1995
DOI: 10.1128/jcm.33.6.1501-1509.1995
|View full text |Cite
|
Sign up to set email alerts
|

Colonizing populations of Candida albicans are clonal in origin but undergo microevolution through C1 fragment reorganization as demonstrated by DNA fingerprinting and C1 sequencing

Abstract: The genetic homogeneity of nine commensal and infecting populations of Candida albicans has been assessed by fingerprinting multiple isolates from each population by Southern blot hybridization first with the Ca3 probe and then with the 0.98-kb C1 fragment of the Ca3 probe. The isolates from each population were highly related, demonstrating the clonal origin of each population, but each population contained minor variants, demonstrating microevolution. Variation in each case was limited to bands of the Ca3 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 24 publications
4
92
1
5
Order By: Relevance
“…The complex Ca3 probe has been used in a large range of epidemiological studies involving significant numbers of strains and was found to be highly effective in assessing microevolution within clonal populations over time, due primarily to the hypervariability of genomic sequences homologous to the C1 fragment of the probe Anderson et al 1993;Schmid et al 1993;Schr€ oppel et al 1994;Lockhart et al 1995Lockhart et al , 1996. The C1 region contains the repetitive DNA sequence (RPS element), which is present at different locations in the C. albicans genome (Iwaguchi et al 1992;Lockhart et al 1995). The microevolutionary changes identified by Ca3 are due to the insertion and deletion of the fulllength RPS elements at specific sites dispersed throughout the genome and thus can be detected after hybridization of genomic DNA with the C1 fragment of Ca3 (Lockhart et al 1995;Pujol et al 1999).…”
Section: Restriction Enzyme Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The complex Ca3 probe has been used in a large range of epidemiological studies involving significant numbers of strains and was found to be highly effective in assessing microevolution within clonal populations over time, due primarily to the hypervariability of genomic sequences homologous to the C1 fragment of the probe Anderson et al 1993;Schmid et al 1993;Schr€ oppel et al 1994;Lockhart et al 1995Lockhart et al , 1996. The C1 region contains the repetitive DNA sequence (RPS element), which is present at different locations in the C. albicans genome (Iwaguchi et al 1992;Lockhart et al 1995). The microevolutionary changes identified by Ca3 are due to the insertion and deletion of the fulllength RPS elements at specific sites dispersed throughout the genome and thus can be detected after hybridization of genomic DNA with the C1 fragment of Ca3 (Lockhart et al 1995;Pujol et al 1999).…”
Section: Restriction Enzyme Analysismentioning
confidence: 99%
“…The C1 region contains the repetitive DNA sequence (RPS element), which is present at different locations in the C. albicans genome (Iwaguchi et al 1992;Lockhart et al 1995). The microevolutionary changes identified by Ca3 are due to the insertion and deletion of the fulllength RPS elements at specific sites dispersed throughout the genome and thus can be detected after hybridization of genomic DNA with the C1 fragment of Ca3 (Lockhart et al 1995;Pujol et al 1999). Moreover, Ca3 hybridization has proven to be reproducible and amenable to computer-assisted analysis.…”
Section: Restriction Enzyme Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…10 They demonstrated that both Cg6 and Cg12 probes discriminate microevolution within sequential isolates of C. glabrata, 10 as observed in clonal population of C. albicans grown over many generations with Ca3 probes. 35,36 The probes also contain invariant sequences which facilitate normalisation in computerassisted analysis that can be used in large epidemiological studies. When analysing diverse geographical collection of 107 clinical isolates, Dodgson et al [11] demonstrated that Cg6 and Cg12, in contrast to RAPD and MLST, discriminate between all isolates in all groups and were the better methods when analysing microevolution or nosocomial transmission.…”
Section: Southern Blot Hybridisationmentioning
confidence: 99%